Transcriptome analysis to unravel the gene expression profile of ovarian follicular development in Magang goose - Mingming LEI; Rong CHEN; Qingming QIN; Huanxi ZHU; Zhendan SHI (The Society for Reproduction and Development, 2020)
Magang geese exhibit a unique characteristic of follicular development, with eight largest orderly arranged pre-ovulatory follicles in the abdominal cavity. However, little is known about the mechanisms underlying this follicular development. This study aimed to compare gene expression profiles of granulosa cells (GCs) at different stages of follicular development and provide comprehensive insights into follicle selection and the mechanisms underlying the well-defined follicle hierarchy in Magang geese. GCs of large white follicles (LWFs), small yellow follicles (SYFs), F8, F4, and F1 were used for RNA-seq analysis; 374, 1117, 791, and 593 genes were differentially expressed in stages LWFs to SYFs, SYFs to F8, F8 to F4, and F4 to F1, respectively, suggesting that these genes contribute to follicle selection and development. Reliability of sequencing data was verified through qPCR analysis of 24 genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathways revealed a complex mechanism that remodels the extracellular matrix and turnover of extracellular matrix components in follicular development and ovulation and involves multiple pathway, such as focal adhesion, adherens junction, and extracellular matrix-receptor interaction. Some unique characteristics were observed during the different follicular development stages. For instance, some differentially expressed genes were enriched in progesterone-mediated oocyte maturation and steroid biosynthesis from stage SYFs to F8, whereas others were enriched in actin cytoskeleton regulation and vascular smooth muscle contraction from stage F4 to F1. These findings enhance our current understanding of GC function and ovarian follicles during the key stages of follicular development.